Mammographic oblique views 45° versus 60° - Obad Kovačević, Dragica (Radiology and oncology (Ljubljana), 2003)
Background. Standard screening mammography includes two views: craniocaudal and mediolateral oblique. In the mediolateral oblique projection a central beam angle can varies between 30° and 60°. Patients and methods. We compare the thickness of the compressed breast, time-current product, exposures and image quality in two different mammographic oblique views: 45° versus 60°. Ourstudy population consisted of 33 women in whom additional 60° films after standard 45° films were obtained for the objective diagnostic reasons. Results. The mean thickness of the compressed breast was significantly lower with an angle of 60° than with an angle of 45° (47.8 vs. 50.7 mm, p<0.01); themean time current product and the mean breast exposure were significantly lower with an angle of 60° than with an angle of 45° (42.6 vs. 46.7 mAs, p<0.01; 0.67 vs. 0.78 mGy, p<0,01). The difference in the image quality has not reached statisticaI significance (but it exists!). Conclusions. By introducing 60° films instead of commonly used 45° films, mammograms of at least the same quality can be obtained with lower radiation dose, which is of great importance when we remind the great radiosensitivity of glandular breasttissue.
Keywords: breast; Breast Diseases; diagnostika; Dojka, bolezni; dojke; Film Dosimetry; Film, dozimetrija; Mammography; Mamografija; Radiation Dosage; Radiation Monitoring; Sevanje, doziranje; Sevanje, monitorski nadzor; Termoluminiscentna dozimetrija; Thermoluminescent Dosimetry